[OP.2C.05] THE ROLE OF ARTERIAL STIFFNESS AND BLOOD PRESSURE VARIATIONS IN MORBIDITY AND MORTALITY IN VERY OLD FRAIL SUBJECTS. THE PARTAGE STUDY. (September 2017) - Mourad, J.; Labat, C.; Gautier, S.; Salvi, P.; Valbusa, F.; Hanon, O.; Toulza, O.; Manckoundia, P.; Zamboni, M.; Rolland, Y.; Benetos, A.
Abstract : Objective: We have previously reported in persons over 80 years old living in nursing homes (PARTAGE study) that low pulse pressure amplification (PPA) an indicator of arterial stiffness, was associated with total mortality and the major cardiovascular (CV) events. In subsequent analyses we have shown that the group of subjects with systolic blood pressure (SBP) <130 mmHg, under >1 antihypertensive drugs, had a greater risk of mortality as compared to all other subjects. More recently, we have demonstrated that orthostatic changes in BP (orthostatic hypotension or orthostatic hypertension) were associated with higher risk for major CV events. The aim of the present analysis was to study the combined effects of all these 3 arterial parameters on total mortality and major CV events. Design and method: This analysis was performed in the subjects of the PARTAGE study with follow-up for 2 years. The parameters were studied by using the cutoff points which according to the results of the previous analyses in this cohort: PPA<18.8% (LowPPA); SBP<130 mmHg under >1 antihypertensive drug (TtSBP<130); changes in systolic BP (both an increase or a decrease of >20 mmHg) between supine and upright position (DeltaSBP>20). Were included in the analysis the subjects (n = 883) with measurements of all these 3 arterial parameters. Age and gender were added in all multivariate models. Results: Low PPA, TtSBP<130 and DeltaSBP>20 were observed in 33%, 38% and 21% of patients respectively. "LowPPA" (HR 1.52 (1.13–2.05); p = 0.006) and "TtSBP<130"(HR 1.71 (1.24–2.35); p = 0.001) were independent determinants of total mortality and major CV events whereas "DeltaSBP>20" was a independent determinant for major CV events only (HR 1.40 (1.05–1.89); p = 0.02). In addition, combination of >1 of these arterial parameters significantly increases the risk of total mortality and major CV events (HR for 2 vs none, 2.12 (1.42–3.16); and HR for 3 vs 0, 2.90 (1.46–5.75). Conclusions: People presenting a vascular profile characterized by high arterial stiffness expressed by low PPA, low BP under combination anti-Htn treatment and significant variability in SBP between supine and upright position were at much higher risk for total mortality and major CV events.